LONG-TERM CHANGE OF RECLAIMED CHESTNUT SOLONETZIC SOILS AFTER SINGLE ROTOR INTERNAL PLOWING - Valery Petrovich Kalinichenko; Vladimir Konstantinovich Sharshak; Vladimir Evgenyevich Zinchenko; Vladimir Vladimirovich Chernenko (Advanced Engineering Research)
Long-term change of the solonetzic salted chestnut soil complex of dry steppe after their agrotechnical improvement with a new facility of rotor plowing and mixing of illuvial and lower layers of soil is studied. Some technical parameters of the devices for soil-meliorative rotor-milling processing are discussed. More than 30 years after a single soil processing by plow PMS-70 at the depth of 40—45 cm, the soil consists of small uniformly sized aggregates. No morphological signs of the solonetzic paedogenesis restoration are revealed. The atmospheric precipitation moisture enters readily the soil, freely soluble salts sink at the depth sufficient for the elimination of their negative effect on the paedogenesis. The quantity of humus in the soil layer of 0—20 cm makes up 3,3 %, in the layer of 20—40 cm — 2,4 %. The quantity of absorbed Na+ in the layer of 20—30 cm is 10,6 % from the soil cation exchange capacity instead of 19,8 % of raw soil. The productivity increase of the agricultural crops makes up 25—60 and more percent to the yield level under the standard agriculture technology during the whole period of monitoring.